Effects of eigen and actual frequencies of soft elastic surfaces on droplet rebound from stationary flexible feather vanes - Zhang, Chengchun; Wu, Zhengyang; Shen, Chun; Zheng, Yihua; Yang, Liang; Liu, Yan; Ren, Luquan (Royal Society of Chemistry, 2020)
The aim of this paper is to investigate the effect of eigenfrequency and the actual frequency of the elastic surface for the droplet rebound. The elastic surface used in this study is the stationary flexible feather vanes. A fluid-structure interaction (FSI) numerical model is proposed to predict the phenomenon, and later is validated by the experimental that the droplets impact the stationary flexible feather vanes. The effect of mass and stiffness of the surface is analysed. First, the suitable combination of mass and stiffness of the surface will enhance the drop rebound. Second, a small mass system with higher eigenfrequency will decrease the minimum contact time. In the last, the actual frequencies of the elastic surface, approximate at 75 Hz, can accelerate the drop rebound for all cases.
Keywords: droplet rebound; actual frequency; eigenfrequency